Botanical and genetic characteristics of Farsetia aegyptia Turra growing in Egypt - Walaa M. Ismail; Amira Abdel Motaal; Nadia M. Sokkar; Ahlam M. El-Fishawy (Faculty of Pharmacy, Cairo University, 2013)
Farsetia aegyptia Turra is a perennial woody desert shrub native to Egypt. It is used by native Bedouins as an anti-diabetic and antispasmodic. Study of the botanical features was carried out for the root, young and old stems, leaf, fruit and seed of the plant. F. aegyptia Turra was characterized by the presence of myrosin cells and non-glandular branched unicellular two-armed hairs in the stem, leaves and fruit, while the root showed sclereids with a wide or narrow lumen and lignified pitted walls. Furthermore, the DNA of the plant was extracted from leaf samples and analysed using ten random decamer primers. A total of 58 random amplified polymorphic DNA (RAPD) markers were identified. Both the botanical study and the DNA fingerprint helped in the identification of the plant.